Person-environment fit: work-related attitudes and behavioral outcomes in continuing care retirement communities - Yen, Wen-Shen (Kansas State University, 2012)
Academics and practitioners alike have studied the concept of person-environment fit (P-E fit) during the last two decades. How well a person fits the work environment may be an effective indicator of attitudes and behaviors in organizations. P-E fit is not completely conceptualized, so existing studies of fit theory have focused only on particular dimensions of fit leading to contradictory results. Therefore, Study 1, using multi-dimensional environment fit, tested relationships among the environment fits, work related attitudes, and outcomes at the individual, group, and organization levels. In addition, Study 2 examined the effect of relationship qualities between hierarchical levels (supervisor-subordinate) and multi-dimensional fit on employee turnover intention. To empirically test the proposed relationships, 288 foodservice employees at continuing care retirement communities (22 facilities) statewide submitted questionnaires. Of these, 261 and 254 were usable in study 1 and study 2, respectively, for further data analysis. The results of structural equation modeling (Study 1) suggested that employee need-supply fit, demand-ability fit, person-group fit, and person-organization fit were positively related to employee need satisfaction. Further, need satisfaction was positively related to outcome variables like work engagement, interpersonal citizenship behavior, and organizational commitment. Results of hierarchical multiple regressions (for Study 2) showed that employee need-supply fit perception related negatively to turnover intention. The study also found that the leader-member exchange relationship moderated the need-supply fit and turnover intention. Thus, a close exchange relationship between leaders and subordinates could keep subordinates from leaving because of a need-supply misfit. Further discussion and managerial implications of the findings along with directions for future studies are provided.
Keywords: Person-environment fit; Needs satisfaction; Work engagement; Customer-oriented behavior; Interpersonal citizenship behavior; Organizational commitment; Behavioral Sciences (0602)